Genome-wide analysis of WD40 protein family and functional characterization of BvWD40-82 in sugar beet - Wu, Zhirui; Zhang, Tingyue; Li, Jinna; Chen, Sixue; Grin, Inga R.; Zharkov, Dmitry O.; Yu, Bing; Li, Haiying (Frontiers in Plant Science, 2023)
Sugar beet is one of the most important sugar crops in the world. It contributes greatly to the global sugar production, but salt stress negatively affects the crop yield. WD40 proteins play important roles in plant growth and response to abiotic stresses through their involvement in a variety of biological processes, such as signal transduction, histone modification, ubiquitination, and RNA processing. The WD40 protein family has been well-studied in Arabidopsis thaliana, rice and other plants, but the systematic analysis of the sugar beet WD40 proteins has not been reported. In this study, a total of 177 BvWD40 proteins were identified from the sugar beet genome, and their evolutionary characteristics, protein structure, gene structure, protein interaction network and gene ontology were systematically analyzed to understand their evolution and function. Meanwhile, the expression patterns of BvWD40s under salt stress were characterized, and a BvWD40-82 gene was hypothesized as a salt-tolerant candidate gene. Its function was further characterized using molecular and genetic methods. The result showed that BvWD40-82 enhanced salt stress tolerance in transgenic Arabidopsis seedlings by increasing the contents of osmolytes and antioxidant enzyme activities, maintaining intracellular ion homeostasis and increasing the expression of genes related to SOS and ABA pathways. The result has laid a foundation for further mechanistic study of the BvWD40 genes in sugar beet tolerance to salt stress, and it may inform biotechnological applications in improving crop stress resilience.